2014
DOI: 10.1111/sum.12132
|View full text |Cite
|
Sign up to set email alerts
|

Sugar beet (Beta vulgarisL.) response to diammonium phosphate and potassium sulphate under saline–sodic conditions

Abstract: Salinity and sodicity are prime threats to land resources resulting in huge economic and associated social consequences in several countries. Nutrient deficiencies reduce crop productivity in salt-affected regions. Soil fertility has not been sustainably managed in salt-affected arid regions. Few researchers investigated the crop responses to phosphorus and potassium interactions especially in saline-sodic soils. A research study was carried out to explore the effect of diammonium phosphorus (DAP) and potassiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 33 publications
0
14
0
1
Order By: Relevance
“…Our findings are also in agreement with that of Ojeniyi et al (2007) who reported that application of N, P, K and animal manure increased the dry weight of tomato as compared to control. Hussain et al (2014) found that application of 150 kg K2O ha -1 promoted sugar beet top yield by 49.2% and fresh root yield by 45.0% over control treatment.…”
Section: Effects Of K On Leaf Dry Weightmentioning
confidence: 92%
“…Our findings are also in agreement with that of Ojeniyi et al (2007) who reported that application of N, P, K and animal manure increased the dry weight of tomato as compared to control. Hussain et al (2014) found that application of 150 kg K2O ha -1 promoted sugar beet top yield by 49.2% and fresh root yield by 45.0% over control treatment.…”
Section: Effects Of K On Leaf Dry Weightmentioning
confidence: 92%
“…Soil fertilization with K singly or in interactions (Table 3 and Table S1) significantly improved sugar beet morphophysiological responses and chlorophyll concentration (SPAD index), particularly with K 180 . Increased salt tolerance has been reported in several crops, including sugar beet, with increased availability of K + in plant tissues [10,12,21,22,56]. Under saline conditions, K + assists the availability of water and phytonutrients [57] to sugar beet plants by deepening the roots into the soil to balance the uptake of nutrients, resulting in higher root dimensions, RFW, and thus yields [12].…”
Section: Discussionmentioning
confidence: 99%
“…Egypt is considered an arid region and possesses about 900,000 hectares (about 25%) of irrigated agricultural land that suffers from the occurrence of salinization [9]. High soil salinity causes adverse effects on different plant responses in terms of morpho-physiology and biochemistry, leading to a severe reduction in crop productivities [10,11]. Soil solutions containing Na + and Cl − ions due to high salinity cause osmotic stress, ionic imbalance, nutrient uptake antagonism (especially Na + with K + ), and damage to cellular membranes and some organelles by producing reactive oxygen species (ROS) [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Reclamation of salt-affected soils through appropriate on-farm fertility management practices serves as a vital tool for the enhancement of crop production (JORDAN et al, 2004). Under salt stress, proper fertilizer applications to the soil can increase crop yields (HUSSAIN et al, 2014). Potassium (K) and phosphorus (P) can be important in minimizing the negative impacts of high salt stress in soils (GARG;GUPTA, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The impacts of P and K fertilizers on soil reclamation and growth of maize and sugar beet were studied in the same area (HUSSAIN et al, 2014;. The present study aimed to further investigate the interactions of P and K and salinity on wheat growth and nutrient uptake in a salinesodic environment.…”
Section: Introductionmentioning
confidence: 99%